Manufacturers Satisfaction on Third Party Logistics Providers’ Service Quality - Khabir Rahmat, Abdul; Faisol, Nasruddin; Aizat Yajid, Adi; Izwan Mohd Badrillah, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
Several authors have acknowledged logistics service quality as the determinant of customer satisfaction. By obtaining customer satisfaction, organizations will gain benefits such as higher profitability, retention of customers, a better reputation, and a better company image. In Malaysia, inconsistencies in logistics service quality are stated as one of the highest issues concerned among the Malaysian manufacturers. Therefore, the main objective of the study is to examine the level of customer satisfaction among manufacturers towards outbound logistics service quality delivered by third-party logistics service providers. Specifically, it undertook to determine whether delivery accuracy, product condition, quality of key contact personnel, responsiveness, and timeliness variables were potential determinants for overall customer satisfaction. A self-administered online and mail questionnaire was selected as a mode of data collection. A sample was gathered from the Federation of Malaysian Manufacturers 2009 directory. 166 responses were received out of 1500 questionnaires distributed. Data were analyzed by using structural equation modelling AMOS software. From the information gathered, 85.1% of the respondents are users of third-party logistics services. Most respondents have a high percentage of using outbound logistics services, more than inbound using logistics services. Key findings exhibit most of the respondents are generally satisfied with overall outbound third-party logistics services. Whereby, 52% of the responses are within the “slightly satisfied” level, and only 3% indicates slightly dissatisfaction with the 3PL services. Based on the means of satisfaction level, responsiveness is the highest rated component, followed by delivery accuracy, while product condition is the lowest ranked component. Furthermore, based on the SEM path significance analysis, it is discovered that responsiveness and timeliness are having a positive significant relationship with customer satisfaction and have a high impact to affect the level of satisfaction. The findings exhibit a similar pattern of timeliness impact towards customer satisfaction with earlier research from the 1990s in developed countries. Whereby, more recent studies in the United States indicate non-significance of timeliness. The results also depict the slow development of Malaysian logistics industries, whereby technical quality or operational issues are still the main concerns among customers. This study aligns with the needs for more exploration and expansion on utilizing more information technology among 3PL providers as to enhance punctuality and responsiveness.